THE VALIDITY OF THE SALE AND PURCHASE CONTRACT WITH SHOPEE PAYLATER AS FINANCIAL TECHNOLOGY IN ISLAMIC LAW - Aulia, Fira; Kurniawati, Fitri (Ekonomi Islam, 2025)
Research aims: This study aims to analyze the validity of sale and purchase contracts using Shopee PayLater as a financial technology instrument from the perspective of Islamic law. Design/Methodology/Approach: This research employs a normative juridical approach with a statute-based method. Data were collected from primary legal materials such as fatwas, laws, and regulations, as well as secondary and tertiary legal sources. The study is descriptive in nature. Research findings: The findings reveal that Shopee PayLater does not meet the requirements set by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) as outlined in Fatwa No. 116/DSN-MUI/IX/2017 concerning Sharia Electronic Money. The feature contains ribawi elements through the imposition of interest (minimum 2.95% per month), a handling fee (1% of the transaction), and a late payment penalty (5% of the total amount), which contradict Islamic principles of fairness and transparency in transactions. Theoretical Contribution/Originality: This research contributes to the ongoing discourse on the intersection of Islamic legal norms and modern financial technology, especially regarding the legal status of Buy Now Pay Later (BNPL) systems in Indonesia. Practitioners/Policy Implications: The findings may serve as a reference for fintech companies, policymakers, and regulators in developing sharia-compliant digital financial products, and encourage re-evaluation of existing BNPL schemes to align with Islamic economic principles. Research Limitations/Implications: This study is limited to the legal analysis based on Indonesian regulations and DSN-MUI fatwas, and does not explore user perspectives or comparative international frameworks. Future research is recommended to include broader empirical and cross-jurisdictional insights.